Soulful simplicity [compact disc, unabridged] : how living with less can lead to so much more - Carver, Courtney (Blackstone Audio, 2017)
We are often on a quest for more, giving in to pressure every day to work more, own more, and do more. In this book, Carver shows us how to pursue practical minimalism so we can create more with less--more space, more time, and even more love. She invites us to look at the big picture, discover what's most important to us, and reclaim lightness and ease by getting rid of all the excess things.